Taxonomic description of a new species of Leucoagaricus and utilization of the Pantone Connect app in classification research - Zhu, Xue-Tai; Zhang, Jinming; Zhang, Guo-Qing; Fan, Jia-Xin; Dang, Yong-Xiang (Phytotaxa, 2024)
A new species, Leucoagaricus brunneorube, is described based on morphological characteristics and phylogenetic analyses. It was discovered at Northwest Normal University in Lanzhou City, Gansu Province, China. Leucoagaricus brunneorube is characterized by its epigeous, with small to medium-sized basidiomata, pileal surface felty and white, densely covered with brownish red to maroon furfuraceous squamules, lamella edge darkens when dry, and stipe glabrous and cylindrical with a prominent bulbous base, bulb turning orange-red when bruised, and basidiospores ellipsoid and lack a germ pore, lamella edge sterile, cheilocystidia clavate, some with crystals at the apex, pleurocystidia absent, clamp connections absent in all tissues . In the process, the Pantone Connect app was used to describe the color of the fruitbody, thereby facilitating an exploration of the app’s potential in accurately describing colors in classification research of macrofungi.